Fabrication of Transferable Perforated Isoporous Membranes on Versatile Solid Substrates via the Breath Figure Method. Issue 16 (28th August 2015) - Wu, Lian‐Wei; Wan, Ling‐Shu; Ou, Yang; Zhu, Liang‐Wei; Xu, Zhi‐Kang
Abstract : Isoporous separation membranes have received considerable attention because of the high‐resolution performance and energy‐saving characteristics. Isoporous membranes prepared by the breath figure method rely on special substrates such as water and ice because solid substrates such as polyethylene terephthalate films, which are widely used in commercial processes, often lead to nonthrough pores. In this work, it is found that highly ordered through‐pore membranes can be fabricated on hydrophilic glass surface when using polymers that are able to form ordered membranes at low concentrations. On the basis of this finding, a facile strategy is proposed to fabricate isoporous membranes on various solid substrates by introducing a water‐soluble polymer interlayer. The multifunctional interlayer promotes the spreading of membrane‐forming solutions, enables the formation of through pores, and simplifies the transfer to macroporous supports to form composite membranes. The versatility of the proposed strategy is verified by using different substrates including highly hydrophobic polytetrafluoroethylene film and using different water‐soluble polymers as the interlayer. Furthermore, the high‐resolution separation performance of the isoporous composite membranes has been demonstrated by the filtration of yeasts under gravitational pressure. Abstract : Porous membranes with a narrow pore size distribution are fabricated via the breath figure method on various solid substrates by introducing a water‐soluble interlayer. This interlayer promotes the spreading of membrane‐forming solutions, enables the formation of through pores, and simplifies the transfer step for composite membranes. Separation results confirm high‐resolution, energy‐saving features of the isoporous membranes.